Pemanfaatan Quick Response Code Berbantuan Aplikasi Canva Sebagai Media Pembelajaran Pada Mata Kuliah Fonologi Program Studi Sastra Indonesia - Padhilah Anasti, Huriyah; Ilaturahmi, Auzi; De Komar, Rein; Pulungan, Alpi Anwar; Annisa Yulfana Nalurita, Baiq; Prihatiningsih, Titiek (Pendidikan Sejarah FKIP Universitas JAMBI, 2025)
Phonology as a linguistic study is used as a subject studied by students at universities. Phonology learning is often considered a difficult subject by some students. Therefore, lecturers as educators must be able to deliver the material well to achieve the expected learning. The biggest challenge in learning phonology is the differences in phonological systems in various languages. The use of learning media in teaching phonology can provide assistance and convenience for students. One learning media that can reach a wide range of references is media using Quick Response Codes (QR codes). QR codes can be utilized through various applications, one of which is the Canva application. This community service activity was carried out on September 23-25, 2025, with a total of 63 students taking the phonology course for the 2025/2026 academic year. The results of the activity showed that utilizing Canva learning media integrated with QR codes provides easy access for students to access various references, materials, and teaching materials for phonology studies. Therefore, such learning media is very necessary to make classes more active, meaningful, and provide experience and knowledge for students.